Proyecto de expansión de la línea de marcas en la división farmacéutica de la empresa ecuaquímica - Bastidas Vinces, Karen Jeaninne (2009)
Our project aims to increase the portfolio of branded products with which the company manages ECUAQUÍMICA as an extensive portfolio of generic products, look for this option to import under the control of the company, from laboratories MINTLAB Chile. In Ecuador, within the pharmaceutical industry, there is a culture of preference for drugs with brand recognition in comparison with the consumption of generic drugs, which is why we believe that this expansion would increase the market share of ECUAQUÍMICA, positioning the same in the target market and become more competitive nationally. This study will show whether it is feasible to expand the portfolio of branded products, enabling us to reach new market segments in the pharmaceutical sector, in addition to competing with strong companies in this industry and earn a percentage of market share, generating an increase in corporate profitability. The research is based on the study of each of the brands that the company offers MINTLAB Ecuador. The result of the analysis will be to choose products with the strongest ECUAQUÍMICA to compete in the pharmaceutical market.